Down-regulated expressed protein HMGB3 inhibits proliferation and migration, promotes apoptosis in the placentas of fetal growth restriction. (February 2019) - Lv, Yan; Lv, Mingming; Ji, Xiaohong; Xue, Lu; Rui, Can; Yin, Lingfeng; Ding, Hongjuan; Miao, Zhijing
Highlights: HMGB3 protein is abnormally down-regulated in the placenta of FGR. HMGB3 regulates the proliferation, migration and apoptosis of trophoblast cells. HMGB3 may function by regulating several genes or interact with 71 proteins. Abstract: Fetal growth restriction (FGR) is one of the major complications of pregnancy, which can lead to serious short-term and long-term diseases. High-mobility group box 3 (HMGB3) has been found to contribute to the development of many cancers. However, the role of HMGB3 in the pathogenesis of FGR is blank. Here, we measured the expression level of HMGB3 in the placenta tissues of six normal pregnancies and five FGR patients by western blotting and quantitative real-time polymerase chain reaction (qRT-PCR). CCK8 assay, transwell assay and flow cytometry were used to detect the functional effects of overexpression and silencing of HMGB3 on the HTR8/SVneo trophoblast cell line. The results showed that the protein levels of HMGB3 were significantly decreased in FGR placentas compared to normal controls, while mRNA levels of HMGB3 were not significantly altered. Furthermore, when overexpressed of protein HMGB3 of the trophoblast cells, the proliferation and migration abilities were significantly promoted, and the apoptosis abilities of these cells were statistically inhibited. Cell functional experiments showed the opposite results when the expression of HMGB3 was silent. And the expression of cell function-related genes PCNA, Ki67, Tp53, Bax, MMP-2 and E-cadherin was observed to show corresponding changes by qRT-PCR. The results of mass spectrometry showed that HMGB3 may directly or indirectly interact with 71 proteins. In summary, our results indicated that HMGB3 might be of very great significance to the pathogenesis of FGR and might play the role by leading the dysfunction of placental villous trophoblast cells and through the interaction with some other proteins.